The anticipated and concurring effects of the EMU: exchange rate volatility, institutions and growth - Michele Bagella; Leonardo Becchetti; Iftekhar Hasan (Bank of Finland, 2004)
Reduced exchange rate volatility and higher and less heterogeneous quality of institutional rules and macroeconomic policies are two of the main (anticipated and concurring) effects expected from a currency union.In this paper we measure the magnitude of these two effects on the Euro area countries, looking at real effective exchange rates (REER) and at different indicators of quality of institutional rules and macroeconomic policies (QIRMP).We find that the first effect is much stronger than the second when we compare relative changes on Euro area countries and the rest of the world in the relevant period.We further evaluate the impact of both effects on economic growth on a larger sample of countries. Our findings show that both have significant impact on levels (more robust) and on rates of growth (weaker) of per capita GDP.
URN:NBN:fi:bof-20140807122
Keywords: 330; real exchange rate; volatility; institutional rules; macroeconomic policy